A Note on Marginal Allocation in Multiple-Server Service Systems - Rolfe, Alan J. (Management Science, 1971)
In this note we consider the allocation of servers to a multiple facility service system. Each facility consists of a number of parallel channels and the arrival processes are Poisson. When service times are constant we prove that marginal allocation is an optimal and easily implemented solution technique and suggest that it is also optimal for exponential service times.